Solid waste services under the public policy universalization of law n. 12.305/2010: a case study - Ravagnani, Christopher Abreu; Oliveira, Jose Carlos de [UNESP] (Univ Caxias Sul, Centro Ciencias Comunicacao, 2018)
This paper characterizes and discusses the effectiveness of the public policy of universalization of solid waste services. Therefore, through the deductive method, a case study was carried out in the Hydrographic Basin Committee of the Rivers Sapucai-Mirim/Grande (CBH-SMG) in order to verify whether the goal of the universalization was achieved. The results show that in several indicators of solid waste services, most municipalities have already reached universalization, which indicates the relevance of the research, so that the CBH-SMG serves as a paradigm for the other hydrographic basins, since solid waste services are a public health factor.
Keywords: Empirical research; Fundamental rights; Public policies; Solid waste; Environment